Existence of positive solutions of second‐order delayed differential system on infinite interval. (6th February 2021) - Ding, Ran; Wang, Fanglei; Yang, Nannan; Ru, Yuanfang
Abstract : The present paper is focused on the analysis on the existence of positive solutions of a second‐order differential system with two delays x 1 ′ ′ ( t ) − a 1 ( t ) x 1 ( t ) + m 1 ( t ) f 1 ( t, x ( t ), x τ ( t ) ) = 0, t > 0, x 2 ′ ′ ( t ) − a 2 ( t ) x 2 ( t ) + m 2 ( t ) f 2 ( t, x ( t ), x τ ( t ) ) = 0, t > 0, x 1 ( t ) = 0, − τ 1 ≤ t ≤ 0, and lim t → ∞ x 1 ( t ) = 0, x 2 ( t ) = 0, − τ 2 ≤ t ≤ 0, and lim t → ∞ x 2 ( t ) = 0 by using two well‐known fixed point theorems.